A method for preparing indium phosphide quantum dots with large Stokes shift

By optimizing the core-shell structure synthesis method of indium phosphide quantum dots, thermal heating nucleation and heating cladding technology are used to solve the energy transfer and reabsorption problems caused by spectral overlap between quantum dots, and efficient and adjustable luminescence performance is achieved.

CN116218510BActive Publication Date: 2025-03-04SHANGHAI JIAOTONG UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111481449.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-06
Publication Date
2025-03-04
Estimated Expiration
2041-12-06

AI Technical Summary

Technical Problem

In practical applications, existing indium phosphide quantum dots have spectral overlap between quantum dots of different luminous wavelengths, resulting in a degradation of performance, making it difficult to achieve high color rendering index and low color temperature values.

Method used

By optimizing the synthesis method of InP core-shell structure, thermal heating nucleation and temperature-raising cladding technology are used to prepare indium phosphide quantum dots with intermediate shell and outer shell layer, and the reaction temperature, time and precursor ratio are controlled to achieve large Stokes displacement and high luminous efficiency.

Benefits of technology

The InP quantum dots have adjustable emission wavelength, quantum efficiency is greater than 90%, half-height width and no energy transfer, effectively suppressing FRET and reabsorption phenomena and improving the performance of white light devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116218510B_ABST
    Figure CN116218510B_ABST
Patent Text Reader

Abstract

The invention discloses an indium phosphide quantum dot with a large Stokes shift and a preparation method thereof, and relates to the technical field of quantum dot materials. The preparation method comprises: isolating an indium precursor from oxygen and water at a first temperature, fully dissolving it, adding a phosphorus precursor and then raising the temperature to a second temperature to react, obtaining an indium phosphide core, then adding a shell precursor, raising the temperature to a third temperature, obtaining a quantum dot of a core-shell structure, and then sequentially adding anion and cation precursors at the third temperature to obtain a quantum dot with an emission peak adjustable between 465 and 650 nm, high quantum efficiency and a large Stokes shift. The quantum dot mainly has a large Stokes shift to suppress self-absorption and non-radiative resonant energy transfer, a wide bandgap shell can effectively passivate surface defects, achieve a high fluorescence quantum efficiency, and the position of the fluorescence emission peak can be adjusted in the visible light range by changing the activity of the precursor, does not contain heavy metal elements such as cadmium and lead, and is relatively friendly to the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of quantum dot materials, and in particular relates to a method for preparing indium phosphide quantum dots with large Stokes shift. Background Art

[0002] Quantum dots (QDs), as a new type of semiconductor nanomaterial, have the characteristics of high quantum yield, narrow half-width, excellent photochemical stability and tunable wavelength due to quantum size effect and quantum confinement effect. They are widely used in quantum dot display, white light devices, solar concentrators, bioluminescent labels and liquid chips and other technical fields. However, the quantum dots currently used contain heavy metal elements such as cadmium or lead, and the toxicity of the elements limits their wide application. Compared with cadmium or lead quantum dots, indium phosphide (InP) has similar optical properties to them, does not contain heavy metal elements, and has less impact on the ecological environment and human health. It can be used as an ideal alternative material for cadmium quantum dots.

[0003] In the prior art, the preparation process of InP core-shell quantum dots is relatively mature, and the performance of the obtained quantum dots is comparable to that of cadmium quantum dots. Although the highest quantum yield of InP quantum dots reported so far is close to 100%, due to the spectral overlap between quantum dots of different luminescent wavelengths, fluorescence resonance energy transfer (FRET) and reabsorption will occur in practical applications, resulting in performance degradation. Specifically, in white light LED devices, red, green and blue light are often mixed to achieve white light, and the FRET and reabsorption caused by the spectral overlap between quantum dots of different colors will make it difficult to obtain white light devices with color coordinates close to positive white light, high color rendering index and low color temperature. In addition, when using fluorescent coded microspheres for multivariate detection, a non-orthogonal relationship will be exhibited between the fluorescent signals of the microspheres and the luminescent material, which increases the complexity and difficulty of coding library construction, and the number of codes is also limited.

[0004] At present, there are two methods to solve the problem of energy transfer and re-absorption: one is to control the distance between different luminescent materials. Some researchers have eliminated energy transfer by surface coating with polymers, which makes the preparation process more complicated; the other is to use luminescent materials with no spectral overlap. Some researchers have achieved large Stokes shift by doping transition metal ions and changing the structural morphology of quantum dots to eliminate energy transfer, but the luminescence efficiency of quantum dots prepared by these methods is low.

[0005] Therefore, technicians in this field are committed to developing indium phosphide quantum dots with large Stokes shift and preparation methods thereof, so as to obtain indium phosphide quantum dots with adjustable emission wavelength, high luminous efficiency, narrow half-width and no energy transfer. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing indium phosphide quantum dots with a large Stokes shift in view of the above technical problems. In order to solve the problems of the prior art, the purpose of the present invention is to optimize the synthesis method of InP core-shell structure, prepare an InP quantum dot with a large Stokes shift, effectively suppress FRET, and realize adjustable luminescence in the visible light range.

[0007] The purpose of the present invention can be achieved by the following scheme:

[0008] The present invention provides a method for preparing indium phosphide quantum dots with a large Stokes shift, the method comprising the following steps:

[0009] S1, mixing an indium precursor, a zinc precursor and a coordination solvent to obtain an indium and zinc precursor solution;

[0010] S2, controlling the temperature of the solution obtained in step S1 to a first temperature, adding a phosphorus precursor, heating to a second temperature and keeping the temperature, to obtain an indium phosphide core solution; the first temperature is 50-80° C., and the second temperature is 150-180° C.;

[0011] S3, adding a shell precursor to the solution obtained in step S2, heating to a third temperature and keeping the temperature, to obtain an indium phosphide quantum dot solution having an intermediate shell layer; the third temperature is 290-320° C.;

[0012] S4, sequentially adding an anion precursor and a cation precursor to the solution obtained in step S3, and keeping the temperature at a third temperature to obtain indium phosphide quantum dots having an intermediate shell layer, an outer shell layer and a large Stokes shift.

[0013] As an embodiment of the present invention, in step S1, after the indium precursor, zinc precursor and coordination solvent are mixed, a protective gas is introduced, and after the initial heating, vacuum is carried out, and then the second step of heating and insulation is carried out, and the protective gas is introduced and the third step of heating is continued to obtain an indium and zinc precursor solution; the protective gas is one or more of a rare gas and nitrogen; the temperature of the initial heating is 100°C, the temperature of the second step of heating is 120°C-140°C, and the insulation time is 1-2h; the temperature of the third step of heating is 200°C. Mixing the indium precursor, zinc precursor and coordination solvent, introducing a protective gas and vacuuming can remove water and oxygen. The indium phosphide core has a strong covalent property, and an aerobic environment is easy to form a surface oxide layer, which is not conducive to further shell coating, resulting in a reduction in luminous efficiency. If vacuuming is started at 120°C, violent boiling will occur, and the solution may be sucked into the gas path of the device. Insulation can ensure that the precursor is fully dissolved. The purpose of heating to 200° C. under a protective atmosphere is to ensure complete dissolution and obtain a clear and stable cationic precursor. Subsequent operations are all carried out under a protective atmosphere.

[0014] As an embodiment of the present invention, the insulation time in step S2 is 10 to 150 minutes; the insulation time in step S3 is 0 to 60 minutes; and the insulation time in step S4 is 0 to 60 minutes. The insulation time in step S3 is preferably 5 to 60 minutes; and the insulation time in step S4 is preferably 5 to 60 minutes. During the insulation process, the shell will grow on the InP core, and the length of time affects the integrity of the shell growth. For example, the quantum dot efficiency and half-width obtained at 20 minutes for the middle shell ZnS are optimal. Due to the high activity of the phosphorus precursor, the reaction nucleation begins at about 140°C. Therefore, the temperature for nucleating InP by the thermal heating method, that is, the second temperature, is controlled between 150-180°C, corresponding to the optimal temperature for different zinc halides to form quantum dots with different luminous wavelengths. The thermal heating method mainly uses the magic size clusters formed during the heating process to transform into the InP quantum dot core. If the temperature is too high, such as the conventional hot injection method, the reaction is generally carried out at 230-280℃, and the uniformity of the particle size of the obtained quantum dots becomes poor. The growth temperature of ZnS at 300℃ can obtain InP / ZnS quantum dots with the best quantum efficiency and half-width, while the optimal reaction temperature of ZnSe is higher, and the quantum efficiency and half-width of the ZnSeS shell are best at 320℃.

[0015] As an embodiment of the present invention, the molar ratio of the zinc precursor to the indium precursor in step S1 is 4.89-6.47:1; and the molar ratio of the phosphorus precursor to the indium precursor in step S2 is 5.6-7.4:1.

[0016] As an embodiment of the present invention, the indium precursor in step S1 is indium trichloride, and the zinc precursor is one or more zinc halides; and the phosphorus precursor in step S2 is tris(dimethylamino)phosphine.

[0017] As an embodiment of the present invention, the solvent in step S1 is oleylamine.

[0018] As an embodiment of the present invention, the shell anion precursor in step S3 includes one or more of octanethiol, dodecanethiol, sulfur / trioctylphosphine (S / TOP), sulfur / oleylamine (S / OAm), and selenium / trioctylphosphine (Se / TOP). The molar ratio of the shell anion precursor to the zinc precursor is 1 to 2:1. Since the emission wavelength of the quantum dots obtained by using zinc chloride as a precursor reaches 580nm, the spectrum of the quantum dots obtained by further heating is severely broadened. In order to prepare quantum dots with good comprehensive performance in the red light range, the intermediate layer structure is adjusted. The growth of the ZnSeS shell promotes the red shift of the quantum dot emission wavelength. A high Se content helps to uniform the particle size and reduce the half-height width of the emission spectrum, and an increase in the S content helps to improve the quantum efficiency. The quantum dots obtained when Se: (Se+S) = 0.5 can relieve the interface stress between the InP and ZnS shells, and obtain quantum dots with suitable half-height width and quantum efficiency.

[0019] As an embodiment of the present invention, the anion precursor in step S4 is sulfur / trioctylphosphine (S / TOP), and the cationic precursor is zinc / oleylamine. The molar ratio of the anion precursor to the cationic precursor is 1:1-2.

[0020] As an embodiment of the present invention, the indium phosphide quantum dots include an indium phosphide core, an intermediate shell layer, and an outer shell layer; the intermediate shell layer is ZnSe x S 1~x Shell layer, X takes a value of 0-1; the outer shell layer is a ZnS shell layer, and the outer shell layer is coated on the intermediate shell layer. When x=1, it is an InP / ZnSe / ZnS structure with low efficiency. When x=0.5, it has both large Stokes shift and efficiency, so X is taken as 0-1. The value of X is preferably 0-0.8, and more preferably 0-0.5. The indium phosphide quantum dots prepared by the present invention have high quantum efficiency and a large Stokes shift. The main purpose of the intermediate shell layer is to eliminate the surface defects of InP and improve the quantum efficiency. In-situ passivation is carried out on the InP surface by using less active octanethiol to eliminate surface defects and improve the quantum yield; then ZnS is uniformly grown on the outer layer using S / TOP with moderate activity to form a thick outer shell layer. The thick outer shell layer is mainly to produce a large Stokes shift.

[0021] As an embodiment of the present invention, the average size of the indium phosphide quantum dots is 9-14 nm.

[0022] As an embodiment of the present invention, the emission peak of the indium phosphide quantum dots is 460-650nm, and the half-width is less than 70nm. The indium phosphide quantum dots prepared by the present invention have high quantum efficiency and large Stokes shift.

[0023] The present invention adopts a thermal nucleation method to obtain core quantum dots with uniform particle size, which is conducive to the uniform growth of subsequent shell layers; the shell layer precursors use oleylamine zinc and S / TOP (Se+S / TOP), which have moderate reactivity. By adding sufficient anion and cation precursors, a thicker passivation layer can be uniformly grown on the periphery of the InP core, thereby improving quantum efficiency while inhibiting energy transfer.

[0024] The present invention mainly focuses on the realization of large Stokes shift. By optimizing the encapsulation method, quantum dots with high quantum efficiency and uniform and perfect thick shell are obtained. The average size of the quantum dots is between 9-14nm, which can effectively inhibit energy transfer. This has been verified in absorption-emission spectrum and energy transfer experiments, which is not shown in the prior art.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. By controlling the reaction temperature, reaction time, and the type and ratio of the precursors, the growth of the InP quantum dot luminescent core and the coating thickness of the shell can be achieved, and quantum dots with uniform particle size, adjustable luminescent wavelength between 465-650nm, quantum efficiency greater than 90% and large Stokes shift can be obtained.

[0027] 2. The present invention adopts the technical route of temperature-increasing nucleation, temperature-increasing shelling and hot injection shelling to prepare InP quantum dot nuclei at a relatively low first temperature, and then coat the surface with an intermediate passivation layer by heating to eliminate surface defects and improve the luminescence efficiency of the quantum dots. Finally, a precursor is added at a third temperature to thicken the shell layer, improve the stability of the quantum dots, increase the Stokes shift and reduce the occurrence of energy transfer.

[0028] 3. In the present invention, the thermal heating method controls the nucleation and growth process of InP quantum dots, which can make the particle size distribution of quantum dots more uniform and the half-peak width of the spectrum narrower. High-temperature encapsulation can form a thicker passivation layer, further improving the optical properties of InP quantum dots. The preparation process of the present invention is simple, low-cost, and highly repeatable, providing a new method and idea for solving the energy transfer problem. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0030] The concept, structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings:

[0031] Figure 1 The fluorescence emission spectra and UV-visible absorption spectra of InP core-shell quantum dots of Examples 1-5 of the present invention are shown;

[0032] Figure 2 TEM morphology images of InP quantum dots of Examples 1-5 of the present invention; wherein a is a TEM morphology image of the quantum dots with a light emission wavelength of 465 nm in Example 1; b is a TEM morphology image of the quantum dots with a light emission wavelength of 512 nm in Example 2; c is a TEM morphology image of the quantum dots with a light emission wavelength of 580 nm in Example 3; d is a TEM morphology image of the quantum dots with a light emission wavelength of 635 nm in Example 4; and e is a TEM morphology image of the quantum dots with a light emission wavelength of 650 nm in Example 5;

[0033] Figure 3 Figure 2 is a graph showing the fluorescence spectra of the solutions of Example 2 and Example 4 before and after mixing, wherein ac is a graph showing the fluorescence spectra of quantum dot solutions of different concentrations before and after mixing; d is a graph showing the fluorescence intensity changes of the three groups of experiments;

[0034] Figure 4 The spectra and morphologies of the indium phosphide quantum dots prepared in Comparative Example 1 of the present invention, wherein a is a fluorescence emission spectrum and a UV-visible absorption spectrum, and b is a TEM morphology;

[0035] Figure 5 These are the spectra and morphologies of the indium phosphide quantum dots prepared in Comparative Example 2 of the present invention, wherein a is the fluorescence emission spectrum and the UV-visible absorption spectrum, and b is the TEM morphology. DETAILED DESCRIPTION

[0036] In order to make the features and advantages of this patent more obvious and easy to understand, the technical solution will be described in detail below in combination with specific implementation examples of the present invention. The described implementation examples are only part of the implementation examples of the present invention, and the protection scope of the present invention includes but is not limited to the implementation examples mentioned in the text.

[0037] Example 1

[0038] In this example, nitrogen is used as the protective gas, indium trichloride and tri(dimethylamino)phosphine are used as the core precursors, and oleylamine is used as the coordination solvent to synthesize the InP core, and then zinc iodide and octanethiol are used as shell precursors to form an InP / ZnS core-shell structure to improve the luminescence efficiency. Finally, zinc iodide and S / TOP are used as precursors to further form a coating shell to prepare InP / ZnS / ZnS quantum dots, such as Figure 1 As shown, the fluorescence emission peak is 465nm, the half-height width is 39nm, the quantum efficiency is 92% and it has a large Stokes shift, which can effectively inhibit energy transfer and reabsorption. The specific steps are as follows:

[0039] (1) Preparation of precursor: 0.34 mmol of indium trichloride, 2.2 mmol of zinc iodide and 5 mL of oleylamine were placed in a 25 mL flask, first heated to 100 °C under a protective gas atmosphere, then vacuumed and heated to 120 °C, maintained for 90 min, then nitrogen was introduced and heated to 200 °C to obtain a uniform and stable cationic precursor;

[0040] (2) Nucleation: After cooling the precursor solution to 60-70° C., a phosphorus precursor (0.45 mL of tris(dimethylamino)phosphine and 1 mL of oleylamine were added and heated to 150° C. and kept warm for 150 min to obtain InP quantum dot cores;

[0041] (3) First shell coating: 0.44 mL of octanethiol was slowly added to the above solution, and then the temperature was raised to 300°C and kept for 20 min. The monomer gradually formed a uniform ZnS shell layer on the surface of the InP core to obtain an InP / ZnS core-shell structure;

[0042] (4) Second shell coating: Add the pre-prepared S / TOP (4 mmol S powder and 2 mL TOP ultrasonically dispersed for about 10 min until completely clarified) to the above solution, and then slowly add oleylamine zinc precursor (4.4 mol zinc iodide dissolved in 5 mL oleylamine) and react at 300 °C for 40 min to form a thick ZnS shell layer.

[0043] (5) Purification: The solution after the reaction is cooled to room temperature, chloroform and ethanol are added in proportion, and the solution is dispersed again with chloroform after centrifugal precipitation. Ethanol is added in the same proportion and centrifuged to precipitate the solution. Finally, the precipitate is dissolved in toluene to obtain purified InP / ZnS / ZnS quantum dots with large Stokes shift.

[0044] Example 2

[0045] In this example, nitrogen is used as the protective gas, indium trichloride and tri(dimethylamino)phosphine are used as the core precursors, and oleylamine is used as the coordination solvent to synthesize the InP core, and then zinc bromide and octanethiol are used as shell precursors to form an InP / ZnS core-shell structure to improve the luminous efficiency. Finally, zinc bromide and S / TOP are used as precursors to further form a coating shell to prepare InP / ZnS / ZnS quantum dots, such as Figure 1 As shown, the fluorescence emission peak is 512nm, the half-height width is 48nm, the quantum efficiency is greater than 90% and it has a large Stokes shift, which can effectively inhibit energy transfer and reabsorption. The specific steps are as follows:

[0046] (1) Preparation of precursor: 0.34 mmol of indium trichloride, 2.2 mmol of zinc bromide and 5 mL of oleylamine were placed in a 25 mL flask, first heated to 100 °C under a protective gas atmosphere, then vacuumed and heated to 120 °C, maintained for 90 min, then nitrogen was introduced and heated to 200 °C to obtain a uniform and stable cationic precursor;

[0047] (2) Nucleation: After cooling the precursor solution to 60-70° C., a phosphorus precursor (0.45 mL of tris(dimethylamino)phosphine and 1 mL of oleylamine were added and heated to 160° C. and kept warm for 15 min to obtain InP quantum dot cores;

[0048] (3) First shell coating: 0.44 mL of octanethiol was slowly added to the above solution, and then the temperature was raised to 300°C and kept for 20 min. The monomer gradually formed a uniform ZnS shell layer on the surface of the InP core to obtain an InP / ZnS core-shell structure;

[0049] (4) Second shell coating: Add the pre-prepared S / TOP (4 mmol S powder and 2 mL TOP ultrasonically dispersed for about 10 min until completely clarified) to the above solution, and then slowly add oleylamine zinc precursor (4.4 mmol zinc bromide dissolved in 5 mL oleylamine) and react at 300 °C for 40 min to form a thick ZnS shell layer.

[0050] (5) Purification: The solution after the reaction is cooled to room temperature, chloroform and ethanol are added in proportion for precipitation, the solution is dispersed again with chloroform after centrifugal precipitation, ethanol is added in the same proportion for centrifugal precipitation, and finally the solution is dissolved in toluene to obtain purified InP / ZnS / ZnS quantum dots with large Stokes shift.

[0051] Example 3

[0052] In this example, nitrogen is used as the protective gas, indium trichloride and tri(dimethylamino)phosphine are used as the core precursors, and oleylamine is used as the coordination solvent to synthesize the InP core, and then zinc chloride and octyl mercaptan are used as shell precursors to form an InP / ZnS core-shell structure to improve the luminous efficiency. Finally, zinc chloride and S / TOP are used as precursors to further form a coating shell to prepare InP / ZnS / ZnS quantum dots, such as Figure 1 As shown, the fluorescence emission peak is 580nm, the half-height width is 70nm, the quantum efficiency is greater than 90% and it has a large Stokes shift, which can effectively inhibit energy transfer and reabsorption. The specific steps are as follows:

[0053] (1) Preparation of precursor: 0.45 mmol of indium trichloride, 2.2 mmol of zinc chloride and 5 mL of oleylamine were placed in a 25 mL flask, first heated to 100 °C under a protective gas atmosphere, then vacuumed and heated to 120 °C, maintained for 90 min, then nitrogen was introduced and heated to 200 °C to obtain a uniform and stable cationic precursor;

[0054] (2) Nucleation: After cooling the precursor solution to 60-70° C., a phosphorus precursor (0.45 mL of tris(dimethylamino)phosphine and 1 mL of oleylamine were added and heated to 180° C. and kept warm for 20 min to obtain InP quantum dot cores;

[0055] (3) First shell coating: 0.44 mL of octanethiol was slowly added to the above solution, and then the temperature was raised to 300°C and kept for 20 min. The monomer gradually formed a uniform ZnS shell layer on the surface of the InP core to obtain an InP / ZnS core-shell structure;

[0056] (4) Second shell coating: Add the pre-prepared S / TOP (4 mmol S powder and 2 mL TOP ultrasonically dispersed for about 10 min until completely clarified) to the above solution, and then slowly add oleylamine zinc precursor (4.4 mmol zinc chloride dissolved in 5 mL oleylamine) and react at 300 °C for 40 min to form a thick ZnS shell layer.

[0057] (5) Purification: The solution after the reaction is cooled to room temperature, chloroform and ethanol are added in proportion, and the solution is dispersed again with chloroform after centrifugal precipitation. Ethanol is added in the same proportion and centrifuged to precipitate the solution. Finally, the precipitate is dissolved in toluene to obtain purified InP / ZnS / ZnS quantum dots with large Stokes shift.

[0058] Example 4

[0059] In this example, nitrogen was used as the protective gas, indium trichloride and tri(dimethylamino)phosphine were used as the core precursors, and oleylamine was used as the coordination solvent to synthesize the InP core. Then zinc chloride and S-Se / TOP were used as the shell precursors to form InP / ZnSe x S 1~x The core-shell structure improves the luminescence efficiency. Finally, zinc chloride and S / TOP are used as precursors to further form a coating shell layer to prepare InP / ZnSe x S 1~x / ZnS quantum dots, such as Figure 1 As shown, the fluorescence emission peak is 635nm, the half-height width is 60nm, the quantum efficiency is greater than 60% and it has a large Stokes shift, which can effectively inhibit energy transfer and reabsorption. The specific steps are as follows:

[0060] (1) Preparation of precursor: 0.45 mmol of indium trichloride, 2.2 mmol of zinc chloride and 5 mL of oleylamine were placed in a 25 mL flask, first heated to 100 °C under a protective gas atmosphere, then vacuumed and heated to 120 °C, maintained for 90 min, then nitrogen was introduced and heated to 200 °C to obtain a uniform and stable cationic precursor;

[0061] (2) Nucleation: After cooling the precursor solution to 60-70° C., a phosphorus precursor (0.45 mL of tris(dimethylamino)phosphine and 1 mL of oleylamine were added and heated to 180° C. and kept warm for 20 min to obtain InP quantum dot cores;

[0062] (3) First shell coating: S-Se / TOP (1.1 mmol S powder, 1.1 mmol Se powder and 1.1 mL TOP were ultrasonically dispersed for about 10 min until completely clarified) was slowly added to the above solution, then the temperature was raised to 320 °C and kept warm for 20 min. The monomer gradually formed a uniform ZnSexS1-x shell layer on the surface of the InP core to obtain an InP / ZnSexS1~x core-shell structure.

[0063] (4) Second shell coating: Add the pre-prepared S / TOP (4 mmol S powder and 2 mL TOP ultrasonic dispersion for about 10 min until completely clear) to the above solution, then slowly add oleylamine zinc precursor (4.4 mmol zinc chloride dissolved in 5 mL oleylamine), react at 300 °C for 40 min to form a thick ZnS shell layer;

[0064] (5) Purification: The solution after the reaction is cooled to room temperature, chloroform and ethanol are added in proportion, centrifuged and precipitated, and then dispersed again with chloroform. Ethanol is added in the same proportion and centrifuged and precipitated. Finally, the precipitate is dissolved in toluene to obtain purified InP / ZnSe with a large Stokes shift. x S 1~x / ZnS quantum dots.

[0065] Example 5

[0066] In this example, nitrogen is used as the protective gas, indium trichloride and tri(dimethylamino)phosphine are used as the core precursors, and oleylamine is used as the coordination solvent to synthesize the InP core, and then zinc chloride and Se / TOP are used as shell precursors to form an InP / ZnSe core-shell structure to improve the luminous efficiency. Finally, zinc chloride and S / TOP are used as precursors to further form a coating shell to prepare InP / ZnSe / ZnS quantum dots, such as Figure 1 As shown, the fluorescence emission peak is 650nm, the half-height width is 54nm, the quantum efficiency is 21% and it has a large Stokes shift, which can effectively inhibit energy transfer and reabsorption. The specific steps are as follows:

[0067] (1) Preparation of precursor: 0.45 mmol of indium trichloride, 2.2 mmol of zinc chloride and 5 mL of oleylamine were placed in a 25 mL flask, first heated to 100 °C under a protective gas atmosphere, then vacuumed and heated to 120 °C, maintained for 90 min, then nitrogen was introduced and heated to 200 °C to obtain a uniform and stable cationic precursor;

[0068] (2) Nucleation: After cooling the precursor solution to 60-70° C., a phosphorus precursor (0.45 mL of tris(dimethylamino)phosphine and 1 mL of oleylamine were added and heated to 180° C. and kept warm for 20 min to obtain InP quantum dot cores;

[0069] (3) First shell coating: Se / TOP (2.2 mmol Se powder and 1.1 mL TOP ultrasonically dispersed for about 10 min until completely clear) was slowly added to the above solution, and then the temperature was raised to 320 °C and kept warm for 20 min. The monomer gradually formed a uniform ZnSe shell layer on the surface of the InP core to obtain an InP / ZnSe core-shell structure.

[0070] (4) Second shell coating: Add the pre-prepared S / TOP (4 mmol S powder and 2 mL TOP ultrasonic dispersion for about 10 min until completely clear) to the above solution, then slowly add oleylamine zinc precursor (4.4 mmol zinc chloride dissolved in 5 mL oleylamine), react at 300 °C for 40 min to form a thick ZnS shell layer;

[0071] (5) Purification: The solution after the reaction is cooled to room temperature, chloroform and ethanol are added in proportion, and the solution is dispersed again with chloroform after centrifugal precipitation. Ethanol is added in the same proportion and centrifuged to precipitate the solution. Finally, the precipitate is dissolved in toluene to obtain purified InP / ZnSe / ZnS quantum dots with large Stokes shift.

[0072] from Figure 1 It can be seen that by using zinc precursors with different halogen elements, the emission wavelength of InP quantum dots can be adjusted from 465nm to 580nm. x S 1~x , the emission wavelength can be further adjusted to 650nm. Figure 2 It can be seen that the prepared quantum dots have a relatively large particle size, about 10 nm. Figure 3 It can be seen that because the prepared quantum dots have a large Stokes shift characteristic, when the quantum dots obtained in Example 2 and Example 4 are mixed, the fluorescence spectra are basically unchanged before and after mixing, indicating that the quantum dots developed in this example can solve the reabsorption and energy transfer between quantum dots.

[0073] Comparative Example 1

[0074] The preparation method of this comparative example is similar to that of Example 2, except that no second shell coating is performed. Figure 4 The fluorescence emission spectrum, UV-visible absorption spectrum and TEM morphology of the indium phosphide quantum dots prepared in this comparative example.

[0075] Experimental test analysis:

[0076] from Figure 4 It can be seen that the luminescence peak of the quantum dot is 512nm and the average particle size is 6.81nm. Without the second shell coating, the obtained quantum dot does not have the large Stokes shift characteristic.

[0077] Comparative Example 2

[0078] The preparation method of this comparative example is similar to that of Example 2, except that the second shell layer precursor used is 1 / 2 of that in Example 2. Figure 5 The fluorescence emission spectrum, UV-visible absorption spectrum and TEM morphology of the indium phosphide quantum dots prepared in this comparative example.

[0079] Experimental test analysis:

[0080] The InP quantum dots prepared by the comparative example method were tested and analyzed, and the luminescence peak of the quantum dots was 512nm and the average particle size was 8.08nm. Obviously, when the shell precursor was reduced to 1 / 2 of that in Example 2, the prepared quantum dots did not have the large Stokes shift characteristic.

[0081] By comparing the data of Examples 2 and 3 with Example 2, it can be found that Example 2 successfully coated a thicker ZnS shell on the indium phosphide core through a step-by-step coating method, obtained a large Stokes shift, and provided a new way to solve the energy transfer and reabsorption problems.

[0082] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing indium phosphide quantum dots with large Stokes shift, characterized in that: The method comprises the following steps: S1, mixing an indium precursor, a zinc precursor and a coordination solvent to obtain an indium and zinc precursor solution; S2, controlling the temperature of the solution obtained in step S1 to a first temperature, adding a phosphorus precursor, heating to a second temperature and keeping the temperature, to obtain an indium phosphide core solution; the first temperature is 50-80° C., and the second temperature is 150-180° C.; S3, adding a shell precursor to the solution obtained in step S2, heating to a third temperature and keeping the temperature, to obtain an indium phosphide quantum dot solution having an intermediate shell layer; the third temperature is 290-320° C.; S4, sequentially adding an anion precursor and a cation precursor to the solution obtained in step S3, and keeping the temperature at a third temperature to obtain indium phosphide quantum dots having an intermediate shell layer, an outer shell layer and a large Stokes shift; In step S1, the coordination solvent is oleylamine, the indium precursor is indium trichloride, and the zinc precursor is one or more of zinc halides; The phosphorus precursor in step S2 is tris(dimethylamino)phosphine; In step S3, the shell precursor is octanethiol; In step S4, the anion precursor is sulfur / trioctylphosphine, the cationic precursor is zinc / oleylamine, and the molar ratio of the anion precursor to the cationic precursor is 1:1-2; The insulation time in step S2 is 10 to 150 min; the insulation time in step S3 is 5 to 60 min; the insulation time in step S4 is 5 to 60 min; The indium phosphide quantum dots include an indium phosphide core, an intermediate shell layer, and an outer shell layer; the intermediate shell layer is ZnSe x S 1~x Shell layer, X takes a value of 0-0.5; the outer shell layer is a ZnS shell layer, and the outer shell layer is coated on the middle shell layer.

2. The method for preparing indium phosphide quantum dots according to claim 1, characterized in that: In step S1, after the indium precursor, the zinc precursor and the coordination solvent are mixed, a protective gas is introduced, and vacuum is evacuated and the temperature is increased and kept warm to obtain an indium and zinc precursor solution; the protective gas is one or more of a rare gas and nitrogen; the heating temperature is 120°C-140°C, and the insulation time is 1-2 h.

3. The method for preparing indium phosphide quantum dots according to claim 1, characterized in that: The average size of the indium phosphide quantum dots is 9-14 nm.

4. The method for preparing indium phosphide quantum dots according to claim 1, characterized in that: The emission peak of the indium phosphide quantum dots is 460-650 nm, and the half-width is less than 70 nm.

Citation Information

Patent Citations

  • InP quantum dot and preparation method thereof

    CN110157407A